TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Estimating fine-scale soil moisture content and wheat yield in drought-heterogeneous farmlands using machine learning regressions on multispectral UAV imagery - Ming-Der Yang; Tung-Ching Su; Yu-Chun Hsu (Computers and Electronics in Agriculture, 2026)

Novel electrochemical sensor for histamine: enhancing food safety with polydopamine-modified crystalline NCU-1 zincophosphate material - Asit Kumar Panda; Yu-Chung Chang; Murugan Thiruppathi; Chun-Ru Hsu; Ching-Ping Lu; Yu-Ru Huang; Ja-an Annie Ho; Chih-Min Wang (Food Research International, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

Altered dynamic functional connectivity of the language network associated with electronegative L5 in patients with mild cognitive impairment - Ping-Song Chou; Sharon Chia-Ju Chen; Mei-Chuan Chou; Chung-Yao Hsu; Meng-Ni Wu; Ching-Kuan Liu; Chiou-Lian Lai (GeroScience, 2026)

Rivers as microplastics gatekeepers: Linking terrestrial inputs to coastal sediment sinks and sources - Ting-Chang Hsu; Ahmad; Gwo-Ching Gong; Jheng-Jie Jiang; Hernando P. Bacosa; Hung-Chu Hsu; Ruei-Feng Shiu (Marine Pollution Bulletin, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

High-throughput toxicological profiling and ToxPi-based prioritization of chemical migrants from recycled paper used in food contact materials - Pei-Shan Chih; Pei-Chun Hsu; Rachelle D. Arcega; Wei-Hsiang Chang; Pei-Chu Tai; Ching-Chang Lee; Trias Mahmudiono; Wan-Ru Wang; Rong-Jane Chen; Hsiu-Ling Chen (Journal of Hazardous Materials, 2026)

High resolution mass spectrometry-based non-targeted analysis for discovery of emerging PFAS from food contact materials with intake estimation and health risk assessment - Chih-Wei Chang; Wan-Yin Kuo; Jen-Yi Hsu; Chien-Wei Hsiung; Huei-Jie Jiang; Ching‑Ping Chang; Pao-Chi Liao (Food Packaging and Shelf Life, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Seismic performance and failure mechanisms of scaled reinforced concrete containment vessels under shake table testing - Chang-Ching Chang; Jiaji Wang; Chiun-lin Wu; Thomas T.C. Hsu; Kalyana B. Nakshatrala; Yi-Lung Mo (Engineering Structures, 2026)

Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Unraveling rainfall-induced accelerated slope deformation through the integration of GNSS, seismic, and hydrologic data in Lantai, Taiwan - Yan-Hong Chen; Ya-Ju Hsu; Hsin-Hua Huang; Kuo-Lung Wang; Rou-Fei Chen; Horng-Yue Chen; Jyr-Ching Hu; Chuen-Fa Ni; Kuo-Jen Chang; Chih-Yu Kuo (Landslides, 2026)
Studying deep-seated catastrophic landslides is challenging due to their complex geological conditions, slow and imperceptible movements, limited real-time monitoring, and difficulties in accurately assessing sliding behavior. We examine slope instability in a deep-seated landslide-prone area located in Lantai, Taiwan, by analyzing the temporal evolutions of slope movement and rainfall. Using a non-invasive automatic monitoring system that integrates the Global Navigation Satellite System, seismic velocity changes derived from ambient noise interferometry, as well as rainfall and groundwater-level records, we investigate rainfall-induced accelerated slope deformation in 2015–2024. Our findings show that acceleration events are triggered when rainfall lasts over 30 h and cumulative rainfall exceeds 200 mm at the study site. Multiple sliding events show a consistent temporal sequence, in which rainfall triggers an immediate dv/v decrease of 2–4%, followed by GNSS horizontal displacement typically in the range of ~10–30 mm within 1–2 days, and a delayed groundwater-level rise of about ~3 m occurring 4–5 days after peak GNSS displacement rate. This time lag suggests the initial slope acceleration is associated with pore-pressure increases within the landslide mass. The one-dimensional hydrological model successfully simulates rainfall infiltration into the groundwater system, enabling prediction of delayed groundwater responses. This integrated monitoring-modeling framework improves hazard assessment and early warning for rainfall-induced deep-seated landslides and is broadly applicable worldwide.

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

PM2.5 exposure and breast cancer risk: Independent and combined effects of ESR1 rs2046210 and FGFR2 rs2981582 in a Taiwanese cohort - Yi-Ching Liaw; Chih-Da Wu; Yi-Chia Liaw; Shu-Yi Hsu; Mu-Rong Chao; Chiung-Wen Hu; Yung-Po Liaw (Environmental Pollution, 2026)

Phylogeny and Taxonomy of the Coral Reef Maidenhair Fern Adiantum capillus‐veneris subsp. lanyuanum (Pteridaceae) in East Asia - Zhi‐Xiang Chang; Tian‐Chuan Hsu; Xinping Qi; Ching Ming Hsieh; Atsushi Ebihara; Yi‐Han Chang; Yao‐Moan Huang; Li‐Yaung Kuo (New Zealand Journal of Botany, 2026)
Adiantum capillus‐veneris is a species with a worldwide distribution, exhibiting considerable morphological variation, with several infraspecific names applied. Among these infraspecific taxa, A. capillus‐veneris subspecies lanyuanum can be easily distinguished from typical A. capillus‐veneris by its small and 1‐pinnate fronds. This form has been recorded from a few insular populations in Taiwan and Japan, typically inhabiting moist and shaded coral reef cliffs. A chloroplast DNA phylogeny further demonstrates that collections of subsp. lanyuanum across different populations formed a well‐supported clade, and also provides evidence of its genetic distinctiveness and differentiation. Further examination of herbarium specimens and field observations found that, in addition to frond morphology, the rhizome scale differences are also useful for distinguishing the two taxa. As a consequence, A. capillus‐veneris subsp. lanyuanum comb. nov. is proposed as the appropriate taxonomic designation of this taxa and a neotype is designated.

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Correction: The impact of climate model sea surface temperature biases on tropical cyclone simulations - Wei-Ching Hsu; Christina M. Patricola-DiRosario; Ping Chang (Climate Dynamics, 2026)

Hybrid machine learning–physics-based modeling and model predictive control of variable refrigerant flow systems in buildings - Po-Ching Hsu; Yunho Hwang (Energy and Buildings, 2026)

Anchoring ultrafine CeO2 nanoparticles and loading TiO2 on reduced graphene oxide for photothermal catalytic elimination of NO and Hg0 - Ji-Ren Zheng; Chung-Shin Yuan; Ching-Ching Hsu; Huazhen Shen; Chung-Hsuang Hung (Journal of Environmental Chemical Engineering, 2026)

Microplastics affect marine snow formation and sinking to the ocean's interior - Madeline Olivia; Wen-Huai Wu; An-Yi Tsai; Hung-Chu Hsu; Gwo-Ching Gong; Ruei-Feng Shiu (Water Research, 2026)

Cu2Te/Au@rGO aerogel as an efficient electrocatalyst for the bimodal electrochemical-colorimetric detection of 4-nitrotoluene - Nandini Nataraj; Agalya Mahalingam; Xinke Liu; Yu-Chien Lin; Ching-Wei Tung; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Closed-loop recovery of nickel sulfate hexahydrate from spent lithium-ion batteries for fabrication high-performances Ni-rich LiNi0.8Co0.1Mn0.1O2 cathode materials - Yola Bertilsya Hendri; Ching-Hsiang Hsu; Jia-Hao Hu; Yi-Shiuan Wu; Amun Amri; Chun-Chen Yang (Chemical Engineering Journal, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Anti-inflammatory glycosides from Gomphandra mollis Merr.: Structural elucidation and mechanistic insights - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Man-Hsiu Chu; Thanh-Vu Nguyen; Truc-Ly Thi Duong; Su-Jung Hsu; Yun-Han Wang; Ngoc-Thac Pham; Bien-Thuy Nguyen Bui; Dang-Khoa Nguyen; Thanh-Hoa Vo; Ta-Wei Liu; et al. (Phytochemistry, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Hydroxy stearic acids suppress pancreatic cancer stemness by targeting STAT3 signaling and mitochondrial proteome regulation - Ching-Feng Chiu; Yuan-Kai Qiu; Wei-Yu Kao; Yen-Hao Su; Wan-Yu Wang; Tung-Wei Hsu; Charupong Saengboonmee; Shao-Wen Hung; Olga G. Mountanea; Charikleia S. Batsika; George Kokotos; Shih-Yi Huang (Food Bioscience, 2025)

Hyperbaric oxygen therapy attenuates carbon monoxide-induced lung injury by restoring mitochondrial dynamics and suppressing Pink1/Parkin-mediated mitophagy - Tzu-Hao Chen; Chien-Chin Hsu; Ching-Ping Chang; Chien-Cheng Huang; Ying-Jan Wang (Environmental Pollution, 2025)

A review of the state-of-the-art data-driven modeling of building HVAC systems - Po-Ching Hsu; Lei Gao; Yunho Hwang; Reinard Radermacher (Energy and Buildings, 2025)

Effects of fertilizers on arsenic accumulation in ratoon rice: implications for human health risks - Kai-Wei Juang; Han-Ting Hsu; Wan-Ting Chiao; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2025)

Exploring community energy cum Aquavoltaics in Taiwan - Sin Yee Tan; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Aquaculture, 2025)

Utilizing natural compounds as ligands to disrupt the binding of SARS-CoV-2 receptor-binding domain to angiotensin-converting enzyme 2, impeding viral infection - Jingyi Wu; Ting-Hsu Chen; Zi-han Shen; May-Jywan Tsai; Max K. Leong; Yan-qiang Huang; Ching-Feng Weng (Phytochemistry Letters, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Corrigendum to “Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan” [J. Hydrol. 649 (2025) 132450] - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Genetic structure and diversity of the red big eye Priacanthus macracanthus in the northwestern Pacific Ocean - Sheng-Tai Hsiao; Yu-Min Ju; Kui-Ching Hsu; Po-Hsun Kuo (Marine Biodiversity, 2025)
Understanding genetic diversity and population structure is essential for effective fisheries management. This study examined the population genetic structure, diversity, and demography of the red big eye Priacanthus macracanthus , a commercially crucial species in the western Pacific and eastern Indian Oceans, by using mitochondrial DNA cytochrome b ( cytb ) gene sequences (1,141 bp). A total of 206 samples were collected from 9 locations, and 101 haplotypes were obtained. Analysis revealed that (1) all haplotypes clustered into two sympatric haplogroups; (2) although the genetic distance between these haplogroups was small, nucleotide substitution patterns indicated distinct evolutionary histories; (3) migration and haplogroup distribution patterns suggested that the two haplogroups may have originated from different sources, eastern Indian Ocean and the western Pacific Ocean; and (4) recent population declines and low nucleotide diversity indicated a need for targeted management strategies. These findings provide valuable insights that can guide fisheries management and future research on the conservation of P. macracanthus populations.

Toxicity evaluation and prioritization of recycled plastic food contact materials using in silico tools - Rachelle D. Arcega; Pei-Shan Chih; Pei-Chun Hsu; Wei-Hsiang Chang; Rong-Jane Chen; Trias Mahmudiono; Ching-Chang Lee; Hsiu-Ling Chen (Journal of Hazardous Materials, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Multi-modal fusion in thermal imaging and MRI for early cancer detection - Ching-Hsien Hsu; C. Pandeeswaran; Elizabeth Jesi V; Rajendra Thilahar C (Journal of Thermal Biology, 2025)

Effects of humidity on photocatalytic oxidation of elemental mercury by rGO-modified CeO2/TiO2: Kinetic analysis and experimental exploration - Ji-Ren Zheng; Chung-Shin Yuan; Ting-Yu Chen; Ching-Ching Hsu; Chung-Hsuang Hung; Huazhen Shen (Journal of Environmental Chemical Engineering, 2025)

Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Carcinogenic air pollutants and breast cancer risk in the Arkansas rural community health study: A nested case-control study - Edgar T. Ellis; Sean G. Young; Rachel Carroll; Shelbie D. Stahr; Gail A. Runnells; Elizabeth A. Grasmuck; L. Joseph Su; Yong-Moon Mark Park; Ping-Ching Hsu (Environmental Pollution, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Anthropogenic drought monitoring using socio-hydrological modeling for surface water deficit: Lessons from Northern Taiwan - Che-You Liu; Pin-Yi Huang; Shao-Yiu Hsu; Ching-Pin Tung; Kuo-Wei Liao (Journal of Hydrology, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Comparative study of LSTM and ANN models for power consumption prediction of variable refrigerant flow (VRF) systems in buildings - Po-Ching Hsu; Lei Gao; Yunho Hwang (International Journal of Refrigeration, 2025)

Dynamic changes in the metabolome and microbiome during Citrus depressa Hayata liquid fermentation - Ta-Wei Liu; Benni Iskandar; Man-Hsiu Chu; Yun-Han Wang; Ting-An Huang; Su-Jung Hsu; Yves S.Y. Hsieh; Ching-Kuo Lee (Food Chemistry, 2025)

Nonlinear finite element model updating and fourier neural operator for digital twin of reinforced concrete containment vessel under seismic excitations - Si Fu; Chang-Ching Chang; Chawit Kaewnuratchadasorn; Jiaji Wang; Chiun-Lin Wu; Yi-Lung Mo; Thomas T.C. Hsu (Engineering Structures, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Rapid and noninvasive estimation of human arsenic exposure based on 4-photo-set of the hand and foot photos through artificial intelligence - Benny Wei-Yun Hsu; Wei-Wen Hsiao; Ching-Yi Liu; Vincent S. Tseng; Chih-Hung Lee (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

The Association Among Urinary Di-(2-ethylhexyl) Phthalate Metabolites, Serum Lipid Profiles, and Serum Apoptotic Microparticles in a Young Taiwanese Population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Ching-Way Chen; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Enhanced selectivity of reactive intermediates by modifying electrodes with layered materials for the green high-salinity wastewater treatment - TsingHai Wang; ZiYing Lu; Ching-An Hsu; Kun Qin (Process Safety and Environmental Protection, 2024)

Self-regenerative Ni/SiO2 for dry reforming of methane (DRM): 1000 h-longevity assessment and operando insights to coke removal under N2 atmosphere - Li-Wei Chen; Kim Hoong Ng; Liang-Ching Hsu (Chemical Engineering Journal, 2024)

Metal-organic framework derived Mn0.2Zn0.8Se/C amalgamated with nitrogen-doped graphene hydrogel for antioxidant trolox detection in food, environmental, and biological samples - Akash Ashokrao Jagtap; Rajalakshmi Sakthivel; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Sayee Kannan Ramaraj; Xinke Liu; Dhanaprabhu Pattappan; Hsu-Wei; Yi-Ting Lai; Ching-Wei Tung; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Cardenolide glycosides sensitize gefitinib-induced apoptosis in non-small cell lung cancer: inhibition of Na+/K+-ATPase serving as a switch-on mechanism - Chi-Min Du; Wohn-Jenn Leu; Yi-Huei Jiang; She-Hung Chan; Ih-Sheng Chen; Hsun-Shuo Chang; Lih-Ching Hsu; Jui-Ling Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Cigarette smoking and prostate cancer aggressiveness among African and European American men - Edgar T. Ellis; Brian J. Fairman; Shelbie D. Stahr; Jeannette T. Bensen; James L. Mohler; Lixin Song; Eboneé N. Butler; L. Joseph Su; Ping-Ching Hsu (Cancer Causes & Control, 2024)
Purpose Smoking is a modifiable lifestyle factor that has not been established as a prostate cancer risk factor, nor emphasized in prostate cancer prevention. Studies have shown that African American (AA) smokers have a poorer cancer prognosis than European Americans (EAs), while having a lower prevalence of heavy smoking. We examined the relationship between cigarette smoking and prostate cancer aggressiveness and assessed racial differences in smoking habits on the probability of high-aggressive prostate cancer. Methods Using data from the North Carolina-Louisiana Prostate Cancer Project ( n = 1,279), prostate cancer aggressiveness was defined as high or low based on Gleason scores, serum prostate-specific antigen levels, and tumor stage. Cigarette smoking was categorized as current, former, or never smokers. Multivariable logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI). Results Self-reported current (OR = 1.99; 95% CI 1.30–3.06) smoking was associated with high-aggressive prostate cancer relative to never smokers. When stratified by self-reported race, the odds of having high-aggressive cancer increased among AA current (OR = 3.58; 95% CI 2.04–6.28) and former smokers (OR = 2.21; 95% CI 1.38–3.53) compared to AA never smokers, but the odds were diminished among the EA stratum ( P self-reported race x smoking status = 0.003). Conclusion Cigarette smoking is associated with prostate cancer aggressiveness, a relationship modulated by self-reported race. Future research is needed to investigate types of cigarettes smoked and metabolic differences that may be contributing to the racial disparities observed.

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Retraction Note: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the nexus between financial development and energy finance through demand- and supply-oriented physical disruption in crude oil - Fengsheng Chien; YunQian Zhang; Ching-Chi Hsu (Environmental Science and Pollution Research, 2024)

Retraction Note: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2024)

Release of lead, copper, zinc from the initial corrosion of brass water meter in drinking water: Influences of solution composition and electrochemical characterization - Ching-Hsuan Hsu; Ding-Quan Ng; Yi-Pin Lin (Environmental Pollution, 2024)

Retraction Note: The impact of high economic growth and technology advancement on extensive energy production in China: evidence using NARDL model - Ching-Chi Hsu; Fengsheng Chien (Environmental Science and Pollution Research, 2024)

Testing the moderated mediation effect of recreation safety climate on the interrelationship of serious leisure, recreation involvement, and flow experience - Tien-Ming Cheng; Ching-Yi Hsu; Shan-Ni Li (Journal of Outdoor Recreation and Tourism, 2024)

Thiol-functionalized black carbon as effective and economical materials for Cr(VI) removal: Simultaneous sorption and reduction - Kamonchanok Huangmee; Liang-Ching Hsu; Yu-Min Tzou; Yen-Lin Cho; Chih-Hao Liao; Heng Yi Teah; Yu-Ting Liu (Journal of Environmental Management, 2024)

Age and dietary restriction modulate mitochondrial quality in quadriceps femoris muscle of male mice - Ting-Rui Zhang; Chun-Hsien Chiang; Tzu-Chieh Hsu; Chih-Yun Wang; Ching-Yi Chen (Biogerontology, 2024)

Longitudinal assessment of oxidative stress markers and their relationship with exposure to PM2.5 and its bound metals in healthy participants - Yuan-Ting Hsu; Ting-Yao Su; Trong-Neng Wu; Wei-Te Wu; Saou-Hsing Liou; Ching-Huang Lai; Shau-Ku Huang (International Journal of Hygiene and Environmental Health, 2024)

Investigation of the Kuroshio-coastal current interaction and marine heatwave trends in the coral habitats of Northeastern Taiwan - Po-Chun Hsu; Rose Angeli Tabanao Macagga; Ching-Yuan Lu; Dorathy Yuan-Jane Lo (Regional Studies in Marine Science, 2024)

A practical lateral spreading pressure model for piles in inclined liquefied ground - Jiunn-Shyang Chiou; Ching-Lin Chen; Jing Ling Ng; Yuan-Man Hsu (Engineering Structures, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Population genetic diversity and structure of the Taiwan endemic cyprinid fish Candidia barbata (Cyprinidae): human intervention - Yu-Min Ju; Jui-Hsien Wu; Po-Hsun Kuo; Kui-Ching Hsu (Hydrobiologia, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Exploring the multifaceted impact of lanthanides on physiological pathways in human breast cancer cells - Yi-Ming Huang; Tsu-Yu Hsu; Ching-Yu Liu; Yu-Chen Hsieh; Kuan-Yun Lai; Ya-Wen Yang; Kai-Yin Lo (Toxicology, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Consumption of the nonnutritive sweetener acesulfame potassium increases central precocious puberty risk - Hung-Tsung Wu; Chi-Chen Chiang; Chung-Teng Wang; Yue-Hwa Chen; Shih-Yuan Hsu; Yang-Ching Chen (Journal of Hazardous Materials, 2024)

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Property rights arrangement and stakeholder networks hindering floating photovoltaics: A case of private open-access ponds in Taiwan - Yi-Chieh Chen; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Energy Policy, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Generation of artificial rainfall events for flood risk assessment in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Wei-Ling Chiang; Dung-Jiang Chiou; Cheng-Wu Chen (Natural Hazards, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

A step toward sustainable development: the nexus of environmental sustainability, technological advancement and green finance: evidence from Indonesia - FengSheng Chien; Ching-Chi Hsu; Massoud Moslehpour; Muhammad Sadiq; Bushra Tufail; Thanh Quang Ngo (Environment, Development and Sustainability, 2023)

Suspended particulate matter-bound per- and polyfluoroalkyl substances (PFASs) in a river-coastal system: Possible correlation with transparent exopolymer particles. - Ruei-Feng Shiu; Hui-Ju Lee; Hung-Te Hsu; Gwo-Ching Gong (Marine Pollution Bulletin, 2023)

Influence of climate finance and natural resource consumption on the mitigation of climate change in developed countries in the Pre-COP26 era - Ching-Chi Hsu (Resources Policy, 2023)

Bacterial bioerosion of bones is a post-skeletonisation phenomenon and appears contingent on soil burial - Gordon Turner-Walker; Aida Gutiérrez Galiacho; Núria Armentano; Ching-Quey Hsu (Quaternary International, 2023)

Effect of polysaccharide derived from dehulled adlay on regulating gut microbiota and inhibiting Clostridioides difficile in an in vitro colonic fermentation model - Bao-Hong Lee; Shih-Ching Huang; Chih-Yao Hou; You-Zuo Chen; Yu-Hsin Chen; Sulfath Hakkim Hazeena; Wei-Hsuan Hsu (Food Chemistry, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

A promising non-fullerene acceptor for near-infrared organic photodetectors operating with low dark current and high response speed - Yu-Ching Huang; Zhi-Hao Huang; Tai-Yung Wang; Priyanka Chaudhary; Jen-Fu Hsu; Kun-Mu Lee (Chemical Engineering Journal, 2023)

Post-administration labeling with Palladium(II) ions enables ICP-MS-based determination of the biodistribution of carbonized nanogels - Hsu-Liang Huang; Chih-Ching Huang; Cheng-Kuan Su (Analytica Chimica Acta, 2023)

NOx removal and copper recovery from the leaching process for waste printed circuit boards: performance evaluation and potential environmental impact assessment - Tse-Lun Chen; Yen-Syun Chen; Pen-Chi Chiang; Yi-Hung Chen; Ching-Hsiang Hsu (Environmental Science and Pollution Research, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Natural resource volatility and financial development during Covid-19: Implications for economic recovery - Ching-Chi Hsu; Ka Yin Chau; FengSheng Chien (Resources Policy, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Amination-mediated nano eye-drops with enhanced corneal permeability and effective burst release for acute glaucoma treatment - Duc Dung Nguyen; Chun-Hsu Yao; Shingjiang Jessie Lue; Chia-Jung Yang; Yun-Han Su; Chih-Ching Huang; Jui-Yang Lai (Chemical Engineering Journal, 2023)

RETRACTED ARTICLE: The impact of high economic growth and technology advancement on extensive energy production in China: evidence using NARDL model - Ching-Chi Hsu; Fengsheng Chien (Environmental Science and Pollution Research, 2023)

Digital elevation models for high-resolution base flood elevation mapping in a densely populated city - Song-Yue Yang; Shaohua Marko Hsu; Ching Hsiao; Che-Hao Chang (Natural Hazards, 2022)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Viscous Flow Fields Induced by the Run-Up of Periodic Waves on Vertical and Sloping Seawalls - Chun-Yuan Lin; Ching-Jer Huang; Tai-Wen Hsu (Journal of Marine Science and Engineering, 2022)
Unsteady two-dimensional Reynolds Averaged Navier-Stokes (RANS) equations coupled with the k−ε turbulence model was developed to simulate the viscous flow field near seawalls. The complex free-surface configuration was captured using the particle level set method (PLSM). An innovative solid-fluid coupling method was employed to mimic the solid-fluid interaction on fixed Cartesian grids. The proposed numerical model was applied to investigate the viscous flow fields induced by periodic waves propagating on three different seawalls, including vertical and steep seawalls, which are commonly designed in Taiwan with slopes of 1:2 and 1:5. The results reveal that the wave run-up height is closely related to Iribarren number and breaking wave. Partial standing wave or asymmetric recirculating cells in front of a steep seawall lose symmetry with increasing slope. The wave pressure on the seawall face increases as the Ursell number or seawall slope increases. The undertow caused by breaking waves has a significant effect on the bottom shear stress in front of the seawall.

The Role of Pericytes in the Articular Environment—a Review - Stefano Negri; Zhao Li; Yiyun Wang; Masnsen Cherief; Qizhi Qin; Jiajia Xu; Mario Armando Gomez Salazar; Ginny Ching-Yun Hsu; Aaron W. James (Current Tissue Microenvironment Reports, 2022)

Challenges and Perspectives on the Use of Pericytes in Tissue Engineering - Ginny Ching-Yun Hsu; Amy Lu; Luiz Bertassoni; Cristiane Miranda Franca (Current Tissue Microenvironment Reports, 2022)

Three-Dimensional Musculoskeletal Model of the Lower Extremity: Integration of Gait Analysis Data with Finite Element Analysis - Kao-Shang Shih; Ching-Chi Hsu (Journal of Medical and Biological Engineering, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Differences in the Composition of Abundant Marine Picoeukaryotes in the Marginal Sea Derived from Flooding - Chih-Ching Chung; Gwo-Ching Gong; Yun-Chi Lin; Ching-Wei Hsu (Frontiers in Marine Science, 2022)
The transient impact of flooding on the community composition of marine picoeukaryotes (PEs, cell size ≤5 μm) in the East China Sea (ECS) was revealed in this study. In a summer without flooding (i.e., July 2009), photosynthetic picoeukaryotes (PPEs) were more abundant in the area covered by the Changjiang River diluted water (CDW, salinity ≤31) than in the non-CDW affected area. According to the 18S ribosomal RNA phylogeny, Alveolata (all from the superclass Dinoflagellata) was the main community component accounting for 72 to 99% of the community at each sampling station during the nonflooded summer. In addition to Dinoflagellata, diatoms or Chlorophyta also contributed a considerable proportion to the PE assemblage at the stations close to the edge of CDW coverage. In July 2010, an extreme flooding event occurred in the Changjiang River basin and led to the CDW covering nearly half of the ECS. In the flooded summer, the abundance of PPEs in the CDW-covered area decreased significantly to less than 1 × 10 4 cells ml -1 . Compared to that during the nonflooded summer, the diversity of the PE composition was increased. While Dinophyceae still dominated the surface waters, Syndiniophyceae, which were represented by the uncultured Marine Alveolata Group (MALV)-I and MALV-II, accounted for a substantial amount in the Dinoflagellata superclass relative to this community composition in the nonflooded summer. Furthermore, a variety of plankton, including Cryptophyta, Haptophyta, Picobiliphyta, the uncultured Marine Stramenopiles (MASTs) and heterotrophic nanoflagellates, were observed. The nutrition modes of these PEs have been reported to be mixotrophic or heterotrophic. Therefore, it was inferred that the potentially mixotrophic and heterotrophic PE compositions might be favored in the marginal sea in the flooded summer.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

RETRACTED ARTICLE: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the nexus between financial development and energy finance through demand- and supply-oriented physical disruption in crude oil - Fengsheng Chien; YunQian Zhang; Ching-Chi Hsu (Environmental Science and Pollution Research, 2021)

Assessing the capacity of renewable power production for green energy system: a way forward towards zero carbon electrification - FengSheng Chien; Quang-Thanh Ngo; Ching-Chi Hsu; Ka Yin Chau; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

COVID-19 fear and volatility index movements: empirical insights from ASEAN stock markets - Muhammad Sadiq; Ching-Chi Hsu; YunQian Zhang; Fengsheng Chien (Environmental Science and Pollution Research, 2021)

Effectiveness of palonosetron versus granisetron in preventing chemotherapy-induced nausea and vomiting: a systematic review and meta-analysis - Yu-Chen Hsu; Ching-Yao Chen; Ka-Wai Tam; Chin-Yu Hsu (European Journal of Clinical Pharmacology, 2021)

Assessing the mechanism of barriers towards green finance and public spending in small and medium enterprises from developed countries - Fengsheng Chien; Quang-Thanh Ngo; Ching-Chi Hsu; Ka Yin Chau; Robina Iram (Environmental Science and Pollution Research, 2021)

Evaluating green innovation and performance of financial development: mediating concerns of environmental regulation - Ching-Chi Hsu; Ngo Quang-Thanh; FengSheng Chien; Li Li; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Molecular survey of selected viral pathogens in wild leopard cats (Prionailurus bengalensis) in Taiwan with an emphasis on the spatial and temporal dynamics of carnivore protoparvovirus 1 - Chen-Chih Chen; Ai-Mei Chang; Wan-Jhen Chen; Po-Jen Chang; Yu-Ching Lai; Hsu-Hsun Lee (Archives of Virology, 2021)

Stranger Things: Organismal Traits of Two Octocorals Associated With Singular Symbiodiniaceae in a High-Latitude Coral Community From Northern Taiwan - Tsai-Hsuan Tony Hsu; Lilian Carlu; Yunli Eric Hsieh; Tzu-Yu Angel Lai; Ching-Wei Wang; Ching-Yun Huang; Shan-Hua Yang; Pei-Ling Wang; Nicolas Sturaro; Vianney Denis (Frontiers in Marine Science, 2020)
Scrutinizing the traits of octocorals that could affect their physiological performance becomes increasingly important as several of these species are observed to become dominant on reefs pressured by the Anthropocene. In the present study, we compare the organismal traits of two branching octocorals Litophyton sp. and Stereonephthya sp. commonly populating in sympatry the high-latitude coral communities of northern Taiwan. Using 13 traits, we describe and compare performance traits in these two symbiotic species that we discuss in light of the association they maintain with their algal partners. Litophyton sp. and Stereonephthya sp. hosted Durusdinium and Gerakladium , respectively. Both genera represent singular associations, with the latter further establishing the first solid report of Gerakladium in octocorals. Traits distinguished two groups explained by the two partnerships considered. Litophyton sp. associated with Durusdinium had significantly higher organic matter, chlorophyll (chl) a , total lipid and lower chl c /chl a ratio than Stereonephthya sp. associated with Gerakladium. The δ 15 N in the host and algae, as well as δ 13 C in the host were also higher in Litophyton species. Although no significant difference was observed in the δ 13 C of the algae, Litophyton sp. presented a significantly higher variance for this trait and for chl a content than Stereonephthya species. Altogether, the traits examined suggested contrasting performances among the two octocorals. Both octocoral species clearly deviate from an autotrophic diet. Litophyton sp. appears to complement its heterotrophic diet with photosynthetically acquired energy, while Stereonephthya sp. tends to be more specialized and benefits relatively little from its symbiotic relationship. Our study calls for greater consideration of the individual variation in octocoral physiology and in the definition of their ecological strategies.

Functional Heterogeneity of Perivascular Precursor Cells - Jiajia Xu; Yiyun Wang; Ching-Yun Hsu; Stefano Negri; Bradley Presson; Bruno Péault; Aaron W. James (Current Tissue Microenvironment Reports, 2020)

Optimization of bund wall height and trigger depth for re‐irrigation in paddy field by deepwater ponding irrigation treatment - Chien‐Lin Huang; Hau‐Lieh Huang; Nien‐Sheng Hsu; Ching‐Wen Chen (Irrigation and Drainage, 2020)
This study develops two models and an algorithm to determine the optimal bund wall height of the paddy field and the trigger depth for re‐irrigation, considering the benefits and costs of the transformation from shallow intermittent irrigation treatment to deepwater ponding irrigation. The models and algorithms are composed of: (i) a hydrologic model for ponding depth simulation in a paddy field; (ii) an optimization model for height design and depth determination in deepwater ponding irrigation; (iii) a real‐coded genetic algorithm for solving the optimization model. The results show that the optimal bund wall height of the paddy field is 27.7 cm and the optimal discount ratio of re‐irrigation depth (i.e. trigger depth divided by the upper limit of ponding depth) is 0.008 in Taiwan, with a unit net benefit of US$18 500 ha¯¹. During the first crop‐growing season (January to May) and the second (June to October), the benefit of groundwater recharge, flood mitigation, saved irrigation quantity and income of paddy rice of deepwater ponding irrigation is increased by 73, 13, 53 and 25% than those of shallow intermittent irrigation treatment, respectively. Furthermore, the total benefit of the second season is 16% better than that of the first. © 2020 John Wiley & Sons, Ltd.

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Bias Adjustment of Satellite Precipitation Estimation Using Ground-Based Observation: Mei-Yu Front Case Studies in Taiwan - Nan-Ching Yeh; Yao-Chung Chuang; Hsin-Shuo Peng; Kuo-Lin Hsu (Asia-Pacific Journal of Atmospheric Sciences, 2020)
The Global Satellite Mapping of Precipitation (GSMaP) was used to estimate the accumulated rainfall in May from the Mei-Yu front in Taiwan. Rainfall estimation from GSMaP during 2002–2017 were evaluated using more than 400 local gauge observations, collected from the Taiwan Central Weather Bureau (CWB). Studies have demonstrated that the GSMaP rainfall estimation estimates can be biased, depending on the target region, elevation, and season. In this experiment, we have evaluated GSMaP over three elevation ranges. The GSMaP systemic errors for each elevation range were identified and corrected using regression analysis. The results indicated that GSMaP estimation can be improved significantly through adjustment over three elevation ranges (elevation less than 50 m, elevation of 50–100 m, and elevation higher than 100 m). For these three elevation ranges, the correlation coefficient between the GSMaP estimations and CWB rainfall data was 0.76, 0.78, and 0.59, respectively. This indicated that the GSMaP estimation was more accurate for low-elevation regions than high-elevation regions. After the proposed approaches were employed to correct the errors, the bias errors were respectively improved by 5.64(13.7%), 7.33(38.4%) and 10.52(31.2%) mm for low-, mid- and high-elevation regions. This study demonstrated that the local correction approaches can be used to improve GSMaP estimation of Mei-Yu rainfall in Taiwan.

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Ultrasonography-Based Qualitative and Quantitative Evaluation Approaches for Pompe Disease - Yueh-Hui Lee; Hong-Jen Chiou; Da-Tian Bau; Dau-Ming Niu; Ting-Rong Hsu; Hsuan-En Huang; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to propose the qualitative and quantitative approaches to evaluate the skeletal muscle ultrasound images of 23 Pompe disease (i.e., acid maltase deficiency, AMD) patients and 14 normal subjects. Methods A cohort of 23 AMD patients and 14 normal subjects has been investigated. We compared the B-mode echo intensity of the rectus femoris muscle with that of its surrounding fat (subcutaneous fat) and proposed a qualitative grading method. Quantitative analysis of the region of interest (ROI) with the echo intensity and the segmented area was also performed. Results Qualitative results showed that AMD patients without clinical symptoms (without undergoing ERT) had the highest distribution of Grade 1, and AMD patients undergoing ERT had the widest distribution of Grade 2, and control group (n = 14) with the highest distribution of Grade 1. Using the segmented area approach, quantitative results showed that AMD patients undergoing ERT had the largest and widest distribution. Meanwhile the control subjects (normal subjects) had the lowest and the narrowest areas. The echo intensity of the segmented ROI of AMD patients undergoing ERT displayed the highest and widest (inhomogeneous) distributions. By contrast, the echo intensity of AMD patients without clinical symptoms was slightly increased and with low inhomogeneity. Conclusion The proposed ultrasonography-based qualitative and quantitative approach may be used to evaluate the severity of muscle destruction for AMD patients. Besides, the quantitative segmented area with regression analysis could help predict the incidence of onset of Pompe disease patients.

Construction of a single nucleotide polymorphism marker based QTL map and validation of resistance loci to bacterial wilt caused by Ralstonia solanacearum species complex in tomato - Il Sheob Shin; Jung-Ching Hsu; Shu-Mei Huang; Jaw-Rong Chen; Jaw-Fen Wang; Peter Hanson; Roland Schafleitner (Euphytica, 2020)
Bacterial wilt (BW), caused by Ralstonia solanacearum species complex is one of the major biotic factors limiting tomato production in the humid tropics. Pyramiding of resistance genes through marker-assisted selection is an efficient way to develop durable BW resistant cultivars. Tomato line ‘Hawaii 7996’ (H7996) is a stable and robust resistance source against various strains of the species complex. Major BW resistance quantitative trait loci (QTLs) Bwr - 12 and Bwr - 6 , and several minor or strain specific QTLs have been coarse-mapped in this line, but none has been fine-mapped and validated. The objective of the current study was to construct a high density genetic map using single-nucleotide polymorphism (SNP) markers derived from genotyping-by-sequencing, fine-map Bwr - 12 and Bwr - 6 and determine the effects of these QTLs using a near isogenic line (NIL) population. A high density genetic map using 1604 SNP markers with an average distance of 0.82 cM was developed for 188 F 9 recombinant inbred lines derived from the cross H7996 × WVa700. A total of seven QTLs associated with BW resistance to race 1-phylotype I ( R. pseudosolanacearum ) or/and race 3-phylotype II ( R. solanacearum ) strains were located on chromosomes 6 ( Bwr - 6.1 , 6.2 , 6.3 and 6.4 ) and 12 ( Bwr - 12.1 , Bwr - 12.2 and Bwr - 12.3 ) with logarithm of odds (LOD) scores of 6.2–15.6 and 6.2–31.1, explaining 14.2–33.4% and 15.9–53.9% of the total phenotypic variation contributed from H7996, respectively. To validate the genetic effects of the two QTL regions, a set of 80 BC 3 F 3 NILs containing different sections of Bwr -6 with or without Bwr -12 was phenotyped for disease severity after challenge with either race 1-phylotype I Pss4 or race 3-phylotype II Pss1632 BW strains over two seasons. Bwr -6.1 specific to Pss4 and Bwr -6.3 specific to Pss1632 were mapped to an interval of 5.0 cM ( P < 0.05) between 6_33,444,000_SLM6-47 and 6_33,868,000_SLM6-124 SNP marker, and to 2.7 cM ( P < 0.01) between positions 6_35,949,000 _SLM6-107 to 6_36,750,000_SLM6-82 marker, respectively. In addition, the specific effect of Bwr -12 for resistance to Pss4 (LOD score of 5.8-16.1, P < 0.01) was confirmed.

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

Spatial variation of abundant picoeukaryotes in the subtropical Kuroshio Current in winter - Ya‐Fan Chan; Chih‐Ching Chung; Gwo‐Ching Gong; Ching‐Wei Hsu (Marine Ecology, 2020)
To understand the importance of picoeukaryotes in the biogeochemical cycle in the subtropical Kuroshio Current, a year‐round survey of the hydrography and the distribution of picoeukaryotes were conducted in four oceanographic cruises from October 2012 to July 2013. In comparison with other seasons, the highest abundancy of photosynthetic picoeukaryotes, with concentrations >10 4 cells/ml, was observed around the eastern boundary of the Kuroshio in the winter. Accordingly, the composition of picoeukaryotes in this cold season was further studied by a metabarcoding analysis of the 18S rRNA gene. The majority of picoeukaryotes comprised Alveolata, followed by Haptophyta and Stramenopiles. Their composition was diverse in the waters affected by the Kuroshio and in the offshore province. For Haptophyta, in contrast to clade A prevailing in the Kuroshio waters, clade B1, which was considered the host of uncultivated diazotrophic cyanobacterium group A (UCYN‐A), appeared only in the offshore area. Similarly, in Stramenopiles, Pseudo‐nitzschia spp. and MAST‐1D, respectively, dominated in the Kuroshio‐influenced and offshore areas. While Alveolata was the most abundant group, the distributions of all lineages were similar. The association between picoeukaryote succession and hydrographic change is yet to be fully understood. Our results will assist future studies on the community composition of picoplankton and their relationship with marine ecology in the region.

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

An Ultrasound-Guided Robotic HIFU Ablation System with Respiration Induced Displacement and Time Delay Compensation - Chih Yu An; Yung Lun Hsu; Ching Shiow Tseng (Journal of Medical and Biological Engineering, 2019)

The Combined Use of Groundwater Quality, Drawdown Index and Land Use to Establish a Multi-Purpose Groundwater Utilization Plan - Ching-Ping Liang; Wen-Shuo Hsu; Yi-Chi Chien; Sheng-Wei Wang; Jui-Sheng Chen (Water Resources Management, 2019)

The impact of climate model sea surface temperature biases on tropical cyclone simulations - Wei-Ching Hsu; Christina M. Patricola; Ping Chang (Climate Dynamics, 2019)

Stable isotope analysis reveals ontogenetic feeding shifts in Pacific blue marlin ( Makaira nigricans ) off eastern Taiwan - Ching‐Tsun Chang; Wei‐Chuan Chiang; Yun‐Chen Chang; Michael K. Musyl; Chi‐Lu Sun; Daniel J. Madigan; Aaron B. Carlisle; Hung‐Hung Hsu; Qi‐Xuan Chang; Nan‐Jay Su; Yuan‐Shing Ho; Chen‐Te Tseng (Journal of Fish Biology, 2019)
To gain a better understanding of the trophic ecology of Pacific blue marlin Makaira nigricans off eastern Taiwan, nitrogen and carbon stable isotopes (δ 15 N and δ 13 C) and Bayesian mixing models were used to explore trophic dynamics and potential ontogenetic feeding shifts across M. nigricans of different size classes. Makaira nigricans samples from east of Taiwan ( n = 213) and Palau ( n = 37), as well as their prey ( n = 70), were collected during 2012 and 2013. Results indicated increases in δ 15 N with size, with values of larger size classes (> 200 cm eye‐to‐fork length; L EF ) significantly higher than those L EF . Values of δ 13 C were negatively correlated with size. Makaira nigricans > 200 cm L EF had the highest estimated trophic position (4.44) and also exhibited ontogenetic changes in trophic position. Large M. nigricans fed more on dolphinfish Coryphaena hippurus and hairtail Trichiurus lepturus , while smaller M. nigricans consumed smaller forage fish ( e.g ., moonfish Mene maculata ) and cephalopods. These changes may relate to greater swimming speeds and vertical habitat use in larger M. nigricans , allowing capture and consumption of larger prey items at higher trophic positions. The high trophic level of M. nigricans east of Taiwan confirms its important role as an apex predator in marine food webs and how ecological role changes with size.

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Comparison of Different Pullout Test Setups for Evaluation of Bone–Implant Interfacial Strength of Anterior Lumbar Interbody Fusion Devices - Ting-Kuo Chang; Ching-Chi Hsu (Journal of Medical and Biological Engineering, 2019)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Impulse Noise Denoising Using Confidence Measure with Non-sequential Process Order for X-Ray Bio-images - Ching-Ta Lu; Jun-Hong Shen; Ling-Ling Wang; Chih-Chan Hsu; Li-Ling Liu (Journal of Medical and Biological Engineering, 2018)

Enhancing the effectiveness of AHP for environmental performance assessment of Thailand and Taiwan’s food industry - Anirut Pipatprapa; Hsiang-Hsi Huang; Ching-Hsu Huang (Environmental Monitoring and Assessment, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Improvement of indoor air quality in pet shop using gaseous chlorine dioxide - Ming-Chun Lu; Da-Ji Huang; Ching-Shan Hsu; Chih-Kuo Liang; Geng-Min Chen (Environmental Monitoring and Assessment, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Catechol-O-Methyltransferase Val158Met Polymorphism on Striatum Structural Covariance Networks in Alzheimer’s Disease - Chiung-Chih Chang; Shih-Jen Tsai; Nai-Ching Chen; Chi-Wei Huang; Shih-Wei Hsu; Ya-Ting Chang; Mu-En Liu; Wen-Neng Chang; Wan-Chen Tsai; Chen-Chang Lee (Molecular Neurobiology, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

An Optimization Study for the Bone-Implant Interface Performance of Lumbar Vertebral Body Cages Using a Neurogenetic Algorithm and Verification Experiment - Chian-Her Lee; Ching-Chi Hsu; Li Chaing (Journal of Medical and Biological Engineering, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

A Feasibility Study Regarding the Potential Use of Silica-Doped Calcium Sulfate Anhydrite as a Bone Void Filler - Man-Ping Chang; Hsiu-Ching Hsu; Wei-Hsing Tuan; Po-Liang Lai (Journal of Medical and Biological Engineering, 2017)

Biomechanical evaluation of reconstruction plates with locking, nonlocking, and hybrid screws configurations in calcaneal fracture: a finite element model study - Ching-Hsuan Chen; Chinghua Hung; Yu-Chun Hsu; Chen-Sheng Chen; Chao-Ching Chiang (Medical & Biological Engineering & Computing, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Caffeine ingestion improves power output decrement during 3-min all-out exercise - Ching-Feng Cheng; Wei-Chieh Hsu; Yu-Hsuan Kuo; Ming-Tsung Shih; Chia-Lun Lee (European Journal of Applied Physiology, 2016)

The disintegrin, trimucrin, suppresses LPS-induced activation of phagocytes primarily through blockade of NF-κB and MAPK activation - Yu-Chun Hung; Chun-Chieh Hsu; Ching-Hu Chung; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Using Free Navigation Reference Points and Prefabricated Bone Plates for Zygoma Fracture Model Surgeries - Tien-Hsiang Wang; Hsu Ma; Ching-Shiow Tseng; Yi-Hong Chou; Kun-Lin Cai (Journal of Medical and Biological Engineering, 2016)

Identification of Microalgae by Laser Desorption/Ionization Mass Spectrometry Coupled with Multiple Nanomatrices - Lung-Hsiang Peng; Binesh Unnikrishnan; Chi-Yu Shih; Tung-Ming Hsiung; Jeng Chang; Pang-Hung Hsu; Tai-Chia Chiu; Chih-Ching Huang (Marine Biotechnology, 2016)

Voltage-Current-Adjusted Low-power Video Decoder Chip Design with Validation for Wireless Panoramic Endoscope - Ching-Hwa Cheng; Sheng-Wei Hsu (Journal of Medical and Biological Engineering, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

Cocaine Withdrawal Impairs mGluR5-Dependent Long-Term Depression in Nucleus Accumbens Shell Neurons of Both Direct and Indirect Pathways - Chiung-Chun Huang; Ying-Ching Liang; Cheng-Che Lee; Kuei-Sen Hsu (Molecular Neurobiology, 2015)

Zerumbone, a ginger sesquiterpene, induces apoptosis and autophagy in human hormone-refractory prostate cancers through tubulin binding and crosstalk between endoplasmic reticulum stress and mitochondrial insult - Mei-Ling Chan; Jui-Wei Liang; Lih-Ching Hsu; Wei-Ling Chang; Shoei-Sheng Lee; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Medical Image Enhancement Using Modified Color Histogram Equalization - Wei-Yen Hsu; Ching-Yao Chou (Journal of Medical and Biological Engineering, 2015)

Age and tectonic evolution of the northwest corner of the West Philippine Basin - Wen-Bin Doo; Shu-Kun Hsu; Yi-Ching Yeh; Ching-Hui Tsai; Ching-Ming Chang (Marine Geophysical Research, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

In planta biocontrol of soilborne Fusarium wilt of banana through a plant endophytic bacterium, Burkholderia cenocepacia 869T2 - Ying-Ning Ho; Hsing-Mei Chiang; Chih-Ping Chao; Ching-Chung Su; Hui-Fang Hsu; Chen-tong Guo; Ju-Liang Hsieh; Chieh-Chen Huang (Plant and Soil, 2015)

Disinfection of herbal spa pool using combined chlorine dioxide and sodium hypochlorite treatment - Ching-Shan Hsu; Da-Ji Huang (Environmental Monitoring and Assessment, 2015)

Disinfection of indoor air microorganisms in stack room of university library using gaseous chlorine dioxide - Ching-Shan Hsu; Ming-Chun Lu; Da-Ji Huang (Environmental Monitoring and Assessment, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

A unique amidoanthraquinone derivative displays antiproliferative activity against human hormone-refractory metastatic prostate cancers through activation of LKB1-AMPK-mTOR signaling pathway - Jui-Ling Hsu; Shih-Ping Liu; Chia-Chung Lee; Lih-Ching Hsu; Yunn-Fang Ho; Hsu-Shan Huang; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

Application of Neural Networks and Optimization Model in Conjunctive Use of Surface Water and Groundwater - Ching-Wen Chen; Chih-Chiang Wei; Hung-Jen Liu; Nien-Sheng Hsu (Water Resources Management, 2014)

Urinary metabolites of di(2-ethylhexyl) phthalate relation to sperm motility, reactive oxygen species generation, and apoptosis in polyvinyl chloride workers - Li-Ping Huang; Ching-Chang Lee; Jer-Pei Fan; Po-Hsiu Kuo; Tung-Sheng Shih; Ping-Chi Hsu (International Archives of Occupational and Environmental Health, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Evaluation and improvement of air quality in school public elevator - Ching-Shan Hsu; Da-Ji Huang (Environmental Monitoring and Assessment, 2014)

Nanomolar Naloxone Attenuates Neurotoxicity Induced by Oxidative Stress and Survival Motor Neuron Protein Deficiency - Ya-Yun Hsu; Yuh-Jyh Jong; Yu-Ting Lin; Yu-Ting Tseng; Shih-Hsien Hsu; Yi-Ching Lo (Neurotoxicity Research, 2014)

Optimal fallow area and location for multifunctional benefits of a paddy field during drought periods - Ching-Wen Chen; Nien-Sheng Hsu; Chieh-Shu Wu (Paddy and Water Environment, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)

Paradigm of Monoterpene (β-phellandrene) Hydrocarbons Production via Photosynthesis in Cyanobacteria - Fiona K. Bentley; Jose Gines García-Cerdán; Hsu-Ching Chen; Anastasios Melis (BioEnergy Research, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

An Adaptation Due to Climate Change in Southwest Coast of Taiwan - Yuan-Jyh Lan; Tai-Wen Hsu; Yue-Chen Lin; Ching-Jer Huang (Coastal Management, 2013)

Skin Permeation of Small-Molecule Drugs, Macromolecules, and Nanoparticles Mediated by a Fractional Carbon Dioxide Laser: The Role of Hair Follicles - Woan-Ruoh Lee; Shing-Chuan Shen; Saleh A. Al-Suwayeh; Hung-Hsu Yang; Yi-Ching Li; Jia-You Fang (Pharmaceutical Research, 2013)

Expression and Biologic Significance of Adiponectin Receptors in Papillary Thyroid Carcinoma - Shih-Ping Cheng; Chien-Liang Liu; Yi-Chiung Hsu; Yuan-Ching Chang; Shih-Yuan Huang; Jie-Jen Lee (Cell Biochemistry and Biophysics, 2013)

Heme oxygenase is involved in H2O2-induced lateral root formation in apocynin-treated rice - Yi-Hsuan Chen; Yun-Yang Chao; Yun Yen Hsu; Ching Huei Kao (Plant Cell Reports, 2013)

Crustal features of the northeastern South China Sea: insights from seismic and magnetic interpretations - Yi-Ching Yeh; Shu-Kun Hsu; Wen-Bin Doo; Jean-Claude Sibuet; Char-Shine Liu; Chao-Shing Lee (Marine Geophysical Research, 2012)

Lipocalin-2 Induces Apoptosis in Human Hepatocellular Carcinoma Cells Through Activation of Mitochondria Pathways - Ming-Hsien Chien; Tsung-Ho Ying; Shun-Fa Yang; Ji-Kuen Yu; Chih-Wei Hsu; Shu-Ching Hsieh; Yi-Hsien Hsieh (Cell Biochemistry and Biophysics, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Glacially derived material in an Inner Mongolian desert lake during Marine Isotope Stage 2 - Kandasamy Selvaraj; Chen‐Tung Arthur Chen; C. Prakash Babu; Jiann‐Yuh Lou; Ching‐Ling Liu; Kenneth J. Hsu (Journal of Quaternary Science, 2012)
Establishing the precise timing of continental glacial dynamics and abrupt high‐latitude climate events is crucial to understanding the causes of global climate change. Here we present multi‐proxy records in a lake sediment core from arid Inner Mongolia (Wuliangsuhai Lake) that show two distinct glacially derived sedimentation events at ∼26.2–21.8 and ∼17.3–11.5k cal a BP. Fine sediments from the Last Glacial Maximum separate these glacially derived coarse sediments. Within these intervals, the occurrence of granite clasts at ∼24–23.5, 17.3–17 and 15.6–14.1k cal a BP implies either sediment discharge by meltwater as well as strong current flow in the Yellow River and/or sediment influx through hill‐slope mass wasting and landsliding from the nearby Yin Mountains. Surface microfeatures of quartz grains and spot elemental analysis of black specks in these intervals, however, indicate that physical weathering is dominant and that the provenance of the rocks is probably from a glacial source. To the best of our knowledge, this is the first time glacier‐derived materials have been detected in any desert lake in the Yellow River basin. The occurrence of granite clasts roughly correlates with Heinrich events in the North Atlantic, suggesting synchronous ice sheet dynamics in high‐ and mid‐latitude regions during the Last Glacial period. Although our data provide unprecedented evidence for the influence of glacier‐related processes in arid Inner Mongolia, further well‐dated records are clearly needed to re‐evaluate the correlative inference drawn between granite clast layers in Wuliangsuhai Lake and Heinrich events in the North Atlantic. Copyright © 2012 John Wiley & Sons, Ltd.

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Heme oxygenase is involved in nitric oxide- and auxin-induced lateral root formation in rice - Yi-Hsuan Chen; Yun-Yang Chao; Yun Yen Hsu; Chwan-Yang Hong; Ching Huei Kao (Plant Cell Reports, 2012)

Lack of association between the genetic variations in the C-reactive protein gene and the risk of psoriasis among the Taiwanese - Ya-Ching Chang; Wei-Ming Wu; Lung-An Hsu (Molecular Biology Reports, 2012)

Specific characters of 16S rRNA gene and 16S–23S rRNA internal transcribed spacer sequences of Xylella fastidiosa pear leaf scorch strains - Chiou-Chu Su; Chung-Jan Chang; Wen-Jen Yang; Shih-Tien Hsu; Kuo-Ching Tzeng; Fuh-Jyh Jan; Wen-Ling Deng (European Journal of Plant Pathology, 2012)

Application of chlorine dioxide for disinfection of student health centers - Ching-Shan Hsu; Ming-Chun Lu; Da-Ji Huang (Environmental Monitoring and Assessment, 2012)

High incidence of acute promyelocytic leukemia specifically induced by N-nitroso-N-methylurea (NMU) in Sprague–Dawley rats - Yun-Ching Chang; Jeng-Dong Hsu; Wea-Lung Lin; Yi-Ju Lee; Chau-Jong Wang (Archives of Toxicology, 2012)

Background K2P Channels KCNK3/9/15 Limit the Budding of Cell Membrane-derived Vesicles - Daniel Tsung-Ning Huang; Naiwen Chi; Shiou-Ching Chen; Ting-Ying Lee; Kate Hsu (Cell Biochemistry and Biophysics, 2011)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Perturbations of the stress-induced GLUT4 localization pathway in slow-twitch muscles of obese Zucker rats - Yu-Ching Chen; Shin-Da Lee; Shin-Ying Hsih; Yung-Pei Hsu; Chia-Hua Kuo; Low-Tone Ho (Journal of Physiology and Biochemistry, 2011)

Effects of Asian Dust Storms on Synechococcus Populations in the Subtropical Kuroshio Current - Chih-Ching Chung; Jeng Chang; Gwo-Ching Gong; Shih-Chieh Hsu; Kuo-Ping Chiang; Chia-Wen Liao (Marine Biotechnology, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Isolation and Identification of a Novel Antioxidant with Antitumour Activity from Serratia ureilytica Using Squid Pen as Fermentation Substrate - Yao-Haur Kuo; Tzu-Wen Liang; Kao-Cheng Liu; Ya-Wen Hsu; Hsiu-Ching Hsu; San-Lang Wang (Marine Biotechnology, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Differential distributions of CSE1L/CAS and E-cadherin in the polarized and non-polarized epithelial glands of neoplastic colorectal epithelium - Wu-Ching Uen; Cheng-Jeng Tai; Shing-Chuan Shen; Woan-Ruoh Lee; Tang-Yi Tsao; Win-Ping Deng; Hung-Yi Chiou; Chung-Huei Hsu; Cheng-I Hsieh; Ching-Fong Liao; Ming-Chung Jiang (Journal of Molecular Histology, 2010)

Editing of accD and ndhF chloroplast transcripts is partially affected in the Arabidopsis vanilla cream1 mutant - Ching-Chih Tseng; Tzu-Ying Sung; Yi-Chiou Li; Shih-Jui Hsu; Chien-Li Lin; Ming-Hsiun Hsieh (Plant Molecular Biology, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Gas seepage, pockmarks and mud volcanoes in the near shore of SW Taiwan - Song-Chuen Chen; Shu-Kun Hsu; Ching-Hui Tsai; Chia-Yen Ku; Yi-Ching Yeh; Yunshuen Wang (Marine Geophysical Research, 2010)

Increase in intrathoracic volume in pectus excavatum patients after the Nuss procedure - Pei-Yeh Chang; Zhen-Yu Hsu; Jin-Yao Lai; Chao-Jan Wang; Yu-Tai Ching (Medical & Biological Engineering & Computing, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Interval number fuzzy linear programming for climate change impact assessments of reservoir active storage - Ching-Pin Tung; Nien-Ming Hong; Ming-hsu Li (Paddy and Water Environment, 2009)

Assessing the impact of climate change on the land hydrology in Taiwan - Ming-Hsu Li; Waiting Tien; Ching-Pin Tung (Paddy and Water Environment, 2009)

Complex genomic organization of Indian muntjac centromeric DNA - Ya-Ming Cheng; Tzai-Shiuan Li; Lie-Jiau Hsieh; Pei-Ching Hsu; Yueh-Chun Li; Chyi-Chyang Lin (Chromosome Research, 2009)

Health Risk of Consuming Heavy Metals in Farmed Tilapia in Central Taiwan - Min-Pei Ling; Hui-Tsung Hsu; Ruei-Hao Shie; Chin-Ching Wu; Yu-Syuan Hong (Bulletin of Environmental Contamination and Toxicology, 2009)

Detection of race 1 strains of Ralstonia solanacearum in field samples in Taiwan using a BIO-PCR method - Chih-Hung Lin; Shih-Tien Hsu; Kuo-Ching Tzeng; Jaw-Fen Wang (European Journal of Plant Pathology, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

Ca-Mg inter-diffusion in synthetic polycrystalline dolomite-calcite aggregate at elevated temperatures and pressure - Wuu-Liang Huang; Teh-Ching Liu; Pouyan Shen; Allen Hsu (Mineralogy and Petrology, 2009)

Effect of metal binding and posttranslational lysine carboxylation on the activity of recombinant hydantoinase - Cheng-Yang Huang; Ching-Chen Hsu; Mei-Chun Chen; Yuh-Shyong Yang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Heat shock-mediated H2O2 accumulation and protection against Cd toxicity in rice seedlings - Yi Ting Hsu; Ching Huei Kao (Plant and Soil, 2007)

Toxicity in leaves of rice exposed to cadmium is due to hydrogen peroxide accumulation - Yi Ting Hsu; Ching Huei Kao (Plant and Soil, 2007)

Meteorologically Adjusted Ground Level Ozone Trends in Southern Taiwan - Kuang-jung Cheng; Che-hui Tsai; Hsu-cherng Chiang; Ching-wen Hsu (Environmental Monitoring and Assessment, 2007)

Application of statistical method in pollution episode analyses - Kuang-Jung Hsu; Ching-Chi Wu (Journal of Atmospheric Chemistry, 2007)

Cadmium-induced oxidative damage in rice leaves is reduced by polyamines - Yi Ting Hsu; Ching Huei Kao (Plant and Soil, 2007)

Identification of USF2 as a key regulator of Runx2 expression in mouse pluripotent mesenchymal D1 cells - Chihuei Wang; Grace Lee; Wayne Hsu; Ching-Hua Yeh; Mei-Ling Ho; Gwo-Jaw Wang (Molecular and Cellular Biochemistry, 2006)

Norepinephrine induces apoptosis in neonatal rat endothelial cells via a ROS-dependent JNK activation pathway - Yun-Ching Fu; Sui-Chu Yin; Ching-Shiang Chi; Betau Hwang; Shih-Lan Hsu (Apoptosis, 2006)

Cadmium-induced ammonium ion accumulation of rice seedlings at high temperature is mediated through abscisic acid - Yi Ting Hsu; Mei Chun Kuo; Ching Huei Kao (Plant and Soil, 2006)

Screening of Compactin-Resistant Microorganisms Capable of Converting Compactin to Pravastatin - Chao-Hsien Chen; Hui-Yu Hu; Yen-Ching Cho; Wen-Hwei Hsu (Current Microbiology, 2006)

Chloroplast sulfate transport in green algae – genes, proteins and effects - Anastasios Melis; Hsu-Ching Chen (Photosynthesis Research, 2005)

Role of SulP, a nuclear-encoded chloroplast sulfate permease, in sulfate transport and H2evolution in Chlamydomonas reinhardtii - Hsu-Ching Chen; A. Jamila. Newton; Anastasios Melis (Photosynthesis Research, 2005)

Localization and function of SulP, a nuclear-encoded chloroplast sulfate permease in Chlamydomonas reinhardtii - Hsu-Ching Chen; Anastasios Melis (Planta, 2004)

Crustal Thinning of the Northern Continental Margin of the South China Sea - Ching-Hui Tsai; Shu-Kun Hsu; Yi-Ching Yeh; Chao-Shing Lee; Kanyuan Xia (Marine Geophysical Research, 2004)

Crustal Structures of the Northernmost South China Sea: Seismic Reflection and Gravity Modeling - Yi-Ching Yeh; Shu-Kun Hsu (Marine Geophysical Research, 2004)

New Bathymetry and Magnetic Lineations Identifications in the Northernmost South China Sea and their Tectonic Implications - Shu-Kun Hsu; Yi-ching Yeh; Wen-Bin Doo; Ching-Hui Tsai (Marine Geophysical Research, 2004)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

SulP , a nuclear gene encoding a putative chloroplast-targeted sulfate permease in Chlamydomonas reinhardtii - Hsu-Ching Chen; Kittisak Yokthongwattana; A. Jamila Newton; Anastasios Melis (Planta, 2003)

Reduced Phagocytosis of Colloidal Carriers Using Soluble CD47 - Yu-Chih Hsu; Marcela Acuña; Stanley M. Tahara; Ching-An Peng (Pharmaceutical Research, 2003)

The Saccharomyces cerevisiae Arr4p is involved in metal and heat tolerance* - Jian Shen; Ching-Mei Hsu; Bae-Kwang Kang; Barry P. Rosen; Hiranmoy Bhattacharjee (BioMetals, 2003)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Blood lead levels of primary-school children in Penghu County, Taiwan: distribution and influencing factors - Tsan Yang; Trong-Neng Wu; Shang-Wei Hsu; Ching-Huang Lai; Kquei-Nu Ko; Saou-Hsing Liou (International Archives of Occupational and Environmental Health, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)

Mapping of 55 new rat microsatellite markers from chromosome-specific libraries - Laurie A. Shepel; Hong Lan; Gerlyn M. Brasic; Megan E. Gheen; Lih-Ching Hsu; Jill D. Haag; Michael N. Gould (Mammalian Genome, 1998)

Inactivation of protein kinase C in rat liver during late hypoglycemic phase of sepsis - Chin Hsu; Hsiao-Ching Jao; Shaw-Lang Yang; Hseng-Kuang Hsu; Maw-Shung Liu (Molecular and Cellular Biochemistry, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)